Risk factors associated with oral Human Papillomavirus (HPV) prevalence within a young adult population - Aimee F. Whitton; Gillian L. Knight; Elizabeth K. Marsh (BMC, 2024)
Abstract Background The prevalence of, and risk factors for, genital Human Papillomavirus (HPV) infections within the young adult population are well-established; the same is not known for oral HPV. This observational study aimed to determine oral HPV prevalence and abundance within a UK young adult population, and examine if sexual practices and established risk factors of oropharyngeal squamous cell carcinomas (OPSCCs) (such as smoking and alcohol consumption) influenced HPV prevalence. Methods Convenience sampling was used to recruit a small sample of 452 UK-based young adults studying at a higher education (HE) institution to the study; the study was not powered. A highly sensitive real-time PCR HPV screening method was developed for the detection of multiple HPV subtypes from oral swabs. HPV-positive samples were subsequently screened by qPCR for viral subtypes HPV-6, HPV-11, HPV-16, HPV-18. Results were analysed by univariate and multivariate methods and stratified for gender, with lifestyle behaviour data collected via questionnaire. Socio-economic status was not captured within the questionnaire. Results We found a high oral HPV prevalence of 22.79%, with a dominance of high-risk viral type HPV-16 (prevalence 19.12%; abundance average 1.08 × 105 copies/million cells) detected within healthy young adults. Frequent smoking (p = .05), masturbation (p = .029), and engagement in multiple sexual activities (p = .057), were found to be associated with oral HPV prevalence, and HPV-16 prevalence, whilst behaviours traditionally associated with genital HPV were not. Conclusions Our results strengthen the link between sexual practices and oral HPV transmission. We suggest that young adults should be considered high-risk for the contraction of oral HPV, although acknowledge that this sample of HE students may not be representative of the wider population. We show that high-risk HPV-16 is prevalent in the healthy population, as well as dominating within OPSCC; this study is one of the first to determine the dominance of oral HPV-16 prevalence and abundance within this population, presenting a clear need for greater awareness of oral HPV infections, and the risk factors for HPV-positive OPSCC within young adults.